2018
DOI: 10.1007/s10067-018-04403-2
|View full text |Cite|
|
Sign up to set email alerts
|

It is time for an organised, scientific approach to the application of patient-reported outcome measures in clinical studies and trials

Abstract: Too often, clinicians and researchers assume that patient-reported outcome measures (PROMs) are simply designed, can be changed to suit specific circumstances and should be freely available for use without seeking permission. If a version is not easily available, they believe they can produce a new translation without relevant experience or expertise. Copyright issues are inconvenient and commonly ignored, despite some journals requesting confirmation from authors that permission had been granted for use of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This convenience combined with their versatility has led to PROs becoming a cornerstone of both clinical evaluation and research in the oncologic patient population [ 2 , 3 ]. However, studies have suggested that the PRO measures are generally limited in their impact as a result of a lack of understanding in the community as to how these measures should be used to inform decision-making [ 4 , 5 ] and a lack of disease-specific tools in oncology [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This convenience combined with their versatility has led to PROs becoming a cornerstone of both clinical evaluation and research in the oncologic patient population [ 2 , 3 ]. However, studies have suggested that the PRO measures are generally limited in their impact as a result of a lack of understanding in the community as to how these measures should be used to inform decision-making [ 4 , 5 ] and a lack of disease-specific tools in oncology [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…While HRQL measures may be useful in evaluating clinical interventions, the true impact of a condition (or role) on an individual should be a holistic assessment of outcome that takes account of both clinical and non-clinical influences on life quality. 24 A widely implemented approach to such measurement in health research is the need-based QoL model. This conceptual model grew out of qualitative research into the impact of depression on the lives of patients.…”
Section: Introductionmentioning
confidence: 99%